1991
DOI: 10.1152/ajpcell.1991.260.3.c609
|View full text |Cite
|
Sign up to set email alerts
|

Length-dependent activation by Ba2+ and Sr2+ of skinned cardiac and skeletal muscle of the rabbit

Abstract: Over a wide range of sarcomere lengths, force activation by Ca2+, Ba2+, and Sr2+ was studied in papillary muscle and in fast skeletal fibers of the gracilis muscle of the rabbit, both skinned by means of freeze drying. The length-tension relations of Ba2+ activation differ significantly from those of Sr2+ and Ca2+ activation with respect to both the value and the position of the maximum. At (almost) full activation, force induced in gracilis muscle by Ba2+ was 50% of the developed force induced by Ca2+. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, the most documented and physiologically useful in the study of activation of contraction, is strontium. Many authors have reported that Sr2+ can substitute for Ca2+ in the activation of tension (Moisescu & Thieleczek 1978, Stephenson & Thieleczek 1986, Grundeman et al 1991.…”
Section: %I E Thod Smentioning
confidence: 99%
“…However, the most documented and physiologically useful in the study of activation of contraction, is strontium. Many authors have reported that Sr2+ can substitute for Ca2+ in the activation of tension (Moisescu & Thieleczek 1978, Stephenson & Thieleczek 1986, Grundeman et al 1991.…”
Section: %I E Thod Smentioning
confidence: 99%